T006 How might brain stimulation enhance consolidation of motor learning?. Issue 3 (March 2017) - Classen, J.; Rumpf, J.-J.
Abstract : Performance increments following a training intervention are secured and sometimes generated by a process termed consolidation. As healthy older humans express lesser consolidation that young people this group might constitute a population particularly well suited to study consolidation. We will review the evidence whether and how brain stimulation enhances consolidation by modulating physiological mechanisms following the training. To demonstrate that brain stimulation is capable to modulate consolidation requires that its effects on performance indices be disambiguated from effects on performance. Transcranial direct current stimulation (tDCS) applied after motor training improved consolidation of explicit motor sequence learning in older controls. Anodal, but not cathodal, tDCS to M1, but not to PMd, led to performance improvements at retesting 8 h after initial learning. Only application of tDCS immediately after the end of training, but not after 1 or 2 h, enhanced offline consolidation. These results will be discussed against evidence provided by others (Tunovic et al., J Neurosci, 2014) that off-line stimulation may rescue consolidation through counteracting activity-dependent decreases of M1 excitability. These findings may suggest a model that brain stimulation may enhance consolidation by preventing post-training inhibitory action in M1 that may originate in premotor cortex.